How does goal framing effect influence household low-carbon behavior: The roles of environmental self-efficacy and global–local identity - Li, Hongbo; Wang, Li; Ou, Yilin; Zhang, Li (Frontiers in Environmental Science, 2023)
Compared to carbon emission reduction from production, the reduction from household is more required. Drawing on the framing effect and social cognitive theory, this study explores the mechanism and boundary condition of the effect of goal framing on household low-carbon behavior. Across two experiments, the study finds that (1) the goal framing of climate change messages affects household low-carbon behavior, in particular, the loss framing elicits greater persuasive impact on household low-carbon behavior than the gain framing; (2) environmental self-efficacy plays a mediating role between the framing effect and household low-carbon behavior. Specifically, the loss framing of climate change messages is more likely to increase residents' environmental self-efficacy than the gain framing, which in turn increases their household low-carbon behavior; (3) residents' global-local identity moderates the effect of the framing messages on household low-carbon behavior. Specifically, among residents with local identity, the loss framing has a more powerful influence on household low-carbon behavior, compared to the gain framing; among residents with global identity, significant difference between the effects of loss and gain framing on household low-carbon behavior is not found. Theoretical and managerial implications of the study are also discussed.